2001
DOI: 10.1002/ps.408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foliar application of phosphonate formulations on the susceptibility of potato tubers to late blight

Abstract: Foliar sprays of potato plants with phosphonic acid (partially neutralised with potassium hydroxide to pH 6.4) substantially reduced infection of the tubers by Phytophthora infestans, the cause of late blight, in glasshouse and field experiments over a 4-year period. Healthy tubers of blight-susceptible cultivars removed from treated plants and artificially inoculated by spraying with sporangial/zoospore suspensions of P infestans did not develop disease symptoms, demonstrating that the phosphonate application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…This study revealed that there was very little variance in the incidence of tuber blight recorded among treatments of fungicides, phosphite, and plant extract combinations at both locations and seasons. In previous research, it was observed that phosphoric acid and other protectant fungicides applied in the field prior to harvest and on harvested tubers can protect potato tubers from P. infestans upon subsequent inoculation (Cooke and Little 2001;Johnson et al 2004). The same studies also demonstrated that foliar applications of phosphoric acid can reduce late blight infections occurring during the growing season (Cooke and Little 2001).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This study revealed that there was very little variance in the incidence of tuber blight recorded among treatments of fungicides, phosphite, and plant extract combinations at both locations and seasons. In previous research, it was observed that phosphoric acid and other protectant fungicides applied in the field prior to harvest and on harvested tubers can protect potato tubers from P. infestans upon subsequent inoculation (Cooke and Little 2001;Johnson et al 2004). The same studies also demonstrated that foliar applications of phosphoric acid can reduce late blight infections occurring during the growing season (Cooke and Little 2001).…”
Section: Discussionmentioning
confidence: 91%
“…The mode of action of phosphonate has been reported to be direct antifungal activity affecting mycelia growth (Fenn and Coffey 1989) and indirect stimulation of host defenses (Guest and Grant 1991). These compounds are also thought to have some systemic characteristics with basipetal and acropetal activity for control of foliar and tuber blight (Cooke and Little 2001). This chemical characteristic allows the compounds to be stable in plants for several weeks and offer long-term protection in potato leaves and tubers (Ouimette and Coffey 1989a;Smillie et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The management of tuber blight has often been accomplished by control of foliage blight involving the use of host plant resistance or fungicide applications (Cooke and Little 2002). Fungicide applications to control foliar late blight and vine kill using desiccants prior to harvest are the most common methods for reducing tuber infection (Stevenson 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium phosphite (KPhi) utilized in the present work is commercialized as a "nutritional compound with antifungal action" (Agro-EMCODI). Several plant species have been treated with phosphites to protect them against pathogens (Cooke and Little 2002;Guest and Grant 1991;Johnson et al 2004;Lobato et al 2008;Ouimette and Coffey 1989;Panicker and Gangadharan 1999;Reuveni et al 2003); however, their mode of action is not completely understood yet. As alkali metal salts of phosphorous acid (H 3 PO 3 ), phosphites can not be directly used by crops as a sole source of nutritional phosphorus (McDonald et al 2001).…”
mentioning
confidence: 99%